Cleft palate lateral synechia syndrome in two patients and literature review. Issue 3 (March 2022) - Plantin, S.; Fabre, M.; Soupre, V.; Guimier, A.; Agostini, V.; Gordon, C.T.; Galliani, E.; Picard, A.; Morice, A.
Abstract: Cleft palate lateral synechia (CPLS) syndrome is an extremely rare congenital malformation syndrome of unknown origin, characterized by the association of cleft palate and one or more intraoral lateral synechiae (OMIM # 119550). Fewer than 20 cases have been described to date. The clinical and histological findings and results of genetic investigations for two additional cases of CPLS are presented herein, in order to better delineate this syndrome, within the context of the relevant literature. The first case presented with a U-shaped cleft palate, bilateral synechiae, and Pierre Robin sequence, requiring early sectioning of the synechiae because of severe feeding problems. The second case presented with a V-shaped cleft palate and a single synechia, running from the left border of the cleft to the floor of the mouth, and was without feeding difficulties. In both cases, histopathological examination of the synechiae revealed an aspect of mucous membranes macroscopically, while staining of sections indicated lymphocyte infiltrates and parakeratosis with stratified squamous epithelium, associated with vessel and connective tissue abnormalities. Sequencing of candidate genes did not identify a genetic cause. Accurate clinical descriptions, histopathological diagnosis, and genetic investigations of patients with synechiae are lacking in the literature. Better characterization of future cases of CPLS will give new insights into its developmental causes.